Monitoring the Impacts of City Sprawling on Urban Agriculture Lands; The Case of Hamadan City, Iran - Hassan Mohammadian Mosammam; Asghar Teimouri (Sustainable Earth Trends)
While the issue of healthy and nutritious food provision for all has become one of the major challenges of global development, urban sprawl increasingly threatening the urban and peri-urban agriculture. However, urban agriculture is one of the most efficient policy to environmental protection, urban resilience and promotion of food security, particularly for poor urban residents. Accordingly, through the analysis of satellite images, using the GIS and remote sensing tools, this paper quantifies the LUCC and urban growth that occurred between 1984 and 2014 in the Hamadan city. It also simulates future urban growth, using CA-Markov Chain Model. The results revealed that urban sprawl over the 1984-2014, led to loss of 3199.5ha of orchards, irrigated and irrigated agricultural lands in Hamadan city. Our simulations suggest that this unsustainable trend will be continued up to 2024. This trends not only threatens urban food security but also will lead to excessive car dependence, poverty increase, loss of local jobs, more pollutions and GHG emission, and result in a decline of city livability. The policies relying on compact city approach, establishing green belt and directing the new growth demand to satellite towns should be advocated.